HUBUNGAN PENDIDIKAN KESEHATAN TENTANG FAKTOR PENYEBAB ASMA DENGAN KEKAMBUHAN ASMA DI RS PKU MUHAMMADIYAH DELANGGU - Tri Yuniarti; . Rejo (KOSALA : Jurnal Ilmu Kesehatan, 2020)
Background. Asthma is a respiratory disease of the respiratory tract. Recurrence of asthma can be triggered by several factors such as environment, food, cold air, and emotion. Health education is an application or application in the field of health in everyday life. Increased health education on the relapse of asthma can be done with health counseling. The Aim of the Study. To determine the relationship of health education about the factors that cause asthma relapse asthma in PKU Muhammadiyah Delanggu General Hospital.Subject and Method. Research subjects were 25 respondents and data were analyzed using Chi Square. Result. Based on analysis test by using chi square analysis with linear alternatives by linear Â x2 = 5.538 and p-value = 0.019 so that there was of significant relation between health education about factor of asthma cause to asthma relapse at PKU Muhammadiyah Delanggu General Hospital (p=0.019). Conclusion: There is a relationship of health education about factors causing asthma to asthma relapse at PKU Muhammadiyah Delanggu General Hospital.Keywords: Asthma, Asthma Relapse, Health EducationÂ Korespondensi: Tri Yuniarti. STIKES Mambaul Ulum Surakarta, Jl.Ring Road Utara KM. 03 Tawangsari, Mojosongo, Jebres Surakarta. Email: yuniartitri3006@gmail.com.